CMHT GP Fortnightly Consultation Clinics – A Pilot Adjunctive Model for GP Access to Mental Health Advice - Mike Apio; Aamenah Hawash (BJPsych Open)
Aims: Assessing the referral patterns, patient characteristics, constraints, immediate and wider benefits of a GP/CMHT fortnightly consultation-liaison clinic as a component of an enhanced community mental health service design.